1997
DOI: 10.1016/s0014-5793(97)00111-7
|View full text |Cite
|
Sign up to set email alerts
|

Terminal oxidases of Azoarcus sp. BH72, a strictly respiratory diazotroph

Abstract: The nitrogen-fixing, grass-associated bacterium Azoarcus sp. BH72 was characterized with respect to its terminal oxidases. Inhibitory respiratory analysis revealed the presence of at least one cytochrome c oxidase and one quinol oxidase. The cytochrome c oxidase was preferably used by the cells under aerobic, whereas the quinol oxidase seemed to be dominant under microaerobic, nitrogen-fixing conditions. Differential spectroscopy and heme analysis of the membrane preparations indicated that the cytochrome c ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Previous biochemical studies suggested the existence of a cbb 3 ‐type cytochrome c oxidase in Azoarcus sp. BH72 (Reinhold‐Hurek and Zhulin, ), which has been corroborated by genome sequence analysis (Krause et al ., ). Oxygen tensions in its host plants appear to be sufficiently low to allow nitrogenase gene expression inside roots of Kallar grass (Hurek et al ., ) and rice (Egener et al ., ).…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Previous biochemical studies suggested the existence of a cbb 3 ‐type cytochrome c oxidase in Azoarcus sp. BH72 (Reinhold‐Hurek and Zhulin, ), which has been corroborated by genome sequence analysis (Krause et al ., ). Oxygen tensions in its host plants appear to be sufficiently low to allow nitrogenase gene expression inside roots of Kallar grass (Hurek et al ., ) and rice (Egener et al ., ).…”
Section: Introductionmentioning
confidence: 68%
“…Biochemical evidence for a branched respiratory chain with cytochrome c oxidase and quinol oxidase has already been reported for Azoarcus sp. BH72 (Reinhold‐Hurek and Zhulin, ). Accordingly, three gene clusters encoding for cytochrome oxidases and two encoding for quinol oxidases were found to be present in the genome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heme extraction and HPLC analysis. Non-covalently-bound hemes were extracted from membrane samples as described previously (23,35,38). Aliquots of membrane preparations were dissolved in 0.5 ml of acetone-HCl (19:1 [vol/vol]) and incubated for 20 min on a rotary mixer.…”
Section: Methodsmentioning
confidence: 99%